Kasus LGBT dalam Negara dan Perspektif Alquran & Tafsir Surah Al A’raf Ayat 80 - Marwah Nazria N Harahap; Risky Munthe; Marzuki Manurung (Medan Resource Center, 2022)
This study aims to discuss the controversial LGBT issue at a time when human rights values ??became the dominant discourse in democratic countries, including Indonesia. In this context, in Indonesia in particular, there has been a discourse contestation between religious teachings on the one hand and new values ??that have emerged due to the strengthening of democratic values, especially the value of human rights. Religious teachings that are repressive towards LGBT have become the target of criticism and are considered to hinder the implementation of the basic values ??possessed by humans, namely freedom. This has strategic value for the religious group itself as well as for its opponents. For religious groups, this rationale can reaffirm their belief in the truth of their religion while for the opponents, this explanation becomes an idea that can be discussed more broadly for consideration of its usefulness in the present.